The Effect of Transformational Leadership Style and MCS to Managerial Performance: The Use of Accounting Information Broad Scope - Amrulloh , M. Faisal; Tianna Solovida, Grace (KnE Social Sciences, 2020)
Transformational leadership style and management control systems may affect the company’s management strategy to ensure the sustainability of the company. Management control system used in this study is the use of a comprehensive performance assessment system and broad scope of use of accounting information. The information generated from both a management control system is used to evaluate the performance and motivate subordinates and used to improve managerial decision making. The purpose of this study was to determine and provide empirical evidence of the influence of transformational leadership style and management control systems on managerial performance through two management control system design is the use of a comprehensive performance assessment system and broad scope of use of accounting information. The object of this study is the division manager or head of the branch company bus transport and travel in the city of Semarang. The number of samples from this study of 35 companies with details of 17 companies and 18 bus transportation company travel transportation. Collecting data in this study conducted using questionnaires and SmartPLS used as a data analysis tool. Keywords: Transformational Leadership Style, MCS, Managerial Performance, Accounting Information